Can a public health intervention improve awareness and health-seeking behaviour for glaucoma?. Issue 12 (6th October 2008) - Baker, H; Murdoch, I E
Abstract : Aim: To investigate whether a public education campaign can increase awareness and change help-seeking behaviour with respect to ocular health in an Indian population. Methods: A health knowledge questionnaire was used investigating and assessing the health campaign. The health campaign comprised four components: (1) television, (2) local press, (3) local radio and (4) places of worship. The target population were Indian residents in Southall, Ealing aged 60+. The aim was to get people to go and have their eyes tested at their local optometric practice. Optometric practices within the borough of Ealing collected sight-test data for the study over 6 months before and after the advertising campaign. Results: The repeat in-depth glaucoma knowledge questionnaire showed a significant increase in the number of people who had heard of glaucoma rising from 22% to 53%. Before intervention, most people had heard about glaucoma from their GP, friend or relative. After intervention, the majority (69%) had heard of glaucoma from the radio. Conclusion: This study has shown a significant increase in awareness from using different kinds of media and has shown radio to be the most effective in our target community. Although the campaign has raised awareness, this study has not shown a change in health-seeking behaviour.